Bis[2,2′-(2-aminoethylimino)di(ethylammonium)] di-μ-sulfido-bis[disulfidostannate(IV)] - Karey, Emma (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, (C(6)H(20)N(4))(2)[Sn(2)S(6)], comprises half of a [Sn(2)S(6)](4−) anion and a diprotonated tris(2-aminoethyl)amine cation. The anion lies on an inversion center, while the atoms of the cation occupy general positions. An intramolecular N—H⋯N hydrogen bond is observed in the cation. In the crystal, strong N—H⋯S hydrogen bonding between the terminal sulfur atoms of the anion and the protonated amine N atoms of the cations result in a three-dimensional network.